2020
DOI: 10.3389/fonc.2020.588557
|View full text |Cite
|
Sign up to set email alerts
|

Intratumor Heterogeneity of MYO18A and FBXW7 Variants Impact the Clinical Outcome of Stage III Colorectal Cancer

Abstract: Many studies failed to demonstrate benefit from the addition of targeted agents to current standard adjuvant FOLFOX chemotherapy in stage III colorectal cancer (CRC) patients. Intratumor heterogeneity may foster the resistant subclones and leads to cancer recurrence. Here, we built a cancer evolution model and applied machine learning analysis to identify potential therapeutic targets. Among 78 CRC cases, whole-genome (WGS) and deep targeted sequencing data generated from paired blood and primary tumor were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…The roles of another member of class XVIII myosins, MYO18A, in oncogenesis remain poorly characterized. A recent study identified frequent MYO18A mutations in stage III CRC [ 59 ]. These mutations appear to be an independent prognostic factor of clinical outcomes and were significantly associated with increased disease-free patient survival [ 59 ].…”
Section: Unconventional Myosinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The roles of another member of class XVIII myosins, MYO18A, in oncogenesis remain poorly characterized. A recent study identified frequent MYO18A mutations in stage III CRC [ 59 ]. These mutations appear to be an independent prognostic factor of clinical outcomes and were significantly associated with increased disease-free patient survival [ 59 ].…”
Section: Unconventional Myosinsmentioning
confidence: 99%
“…A recent study identified frequent MYO18A mutations in stage III CRC [ 59 ]. These mutations appear to be an independent prognostic factor of clinical outcomes and were significantly associated with increased disease-free patient survival [ 59 ]. Since the CRC-associated mutations of MYO18A have not been linked to altered expression or activity of this protein, it is difficult to establish whether their beneficial effect is due to the loss- or gain-of-function of MYO18A.…”
Section: Unconventional Myosinsmentioning
confidence: 99%
“…The survival rate of metastatic CRC patients beyond five years from diagnosis remains less than 20% [1], and approximately 40% of non-metastatic tumors will recur after completing surgical resection [1]. With the notable exception of BRAF V600E mutant tumors [5], other solid tumors targeted therapies (such as tyrosine kinase inhibitors, and immune therapies) have shown little benefit in CRC [6][7][8]. Existing evidence suggests that intra-tumor genetic, epigenetic, and transcriptomic heterogeneity among tumor subclones causes poor prognosis, metastasis, tumor recurrence, and drug resistivity of the CRC patients [7,[9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…With the notable exception of BRAF V600E mutant tumors [5], other solid tumors targeted therapies (such as tyrosine kinase inhibitors, and immune therapies) have shown little benefit in CRC [6][7][8]. Existing evidence suggests that intra-tumor genetic, epigenetic, and transcriptomic heterogeneity among tumor subclones causes poor prognosis, metastasis, tumor recurrence, and drug resistivity of the CRC patients [7,[9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…With advances in NGS technology, tumor-targeted sequencing is becoming an affordable tool for patients with cancer. Indeed, these advances enhanced our ability to identify the impact of tumor heterogeneity and evolution when developing drug response genetic markers in our previous study [ 16 ]. To address these issues, we performed a cancer genomics evolutionary trajectory analysis.…”
Section: Discussionmentioning
confidence: 99%